علاقة طول الجذع والطرف السفلي بالقوة الانفجارية لطالبات كلية التربية الرياضية بجامعة تشرين - زيزفون فادي; محمود بلال; أيوب رنا أحمد (Latakia University Journal -Medical Sciences Series, 2014)
هدفت الدراسة إلى التعرف على بعض القياسات الجسمية المختارة (طول الجذع مع الرأس، طول الطرف السفلي) والقوة الانفجارية والعلاقة بينهما وأثر البرنامج العملي للفصل الأول للكلية على كل من القوة الانفجارية والقياسات الجسمية المختارة لدى طالبات السنة الأولى في كلية التربية الرياضية جامعة تشرين. ولتحديد ذلك أجريت الدراسة على عينة قوامها (45) طالبة واستخدم المنهج الوصفي والمنهج لشبه التجريبي، وجمعت القياسات الجسمية المختارة وكذلك اختبار القفز العمودي من الثبات ،وأظهرت الدراسة نتائج أهمها : وجود علاقة معنوية بين القوة الانفجارية وطول الطرف السفلي .كذلك أظهرت النتائج عدم وجود علاقة ارتباط بين القوة الانفجارية وطول الجذع مع الرأس . وأوصى الباحث بضرورة الاهتمام بمعايير القياسات الجسمية كمعايير للقبول في اختصاصات التربية البدنية والاستفادة من العلاقات الارتباطية بين القياسات الجسمية وعناصر اللياقة البدنية في تنمية وتطوير القابليات والمهارات الحركية . The study aimed to identify some of the selected anthropometric measurements and the explosive strength and the relationship between them in addition to the impact of practical program for the first semester of college on each of the explosive strength and the selected anthropometric measurements of the female students in the first year in the Faculty of Physical Education at Tishreen University. To determine that, the study was conducted on a sample of (45) students and used the descriptive approach, and collected physical measurements as well as selected vertical jump test of fortitude. The study showed the following results: The existence of a correlation between the explosive power and the length of the lower limb and, a lack of correlation between the explosive strength and the length of the trunk with the head. The researcher recommended that attention should be payed to the standards of physical measurements as criteria for admission to the terms of reference for physical education .The researcher also recommended the faculty can take advantage of the connectivity relations between measurements and physical fitness components in the development of motor skills and capabilities.